Detection of intermolecular transferred NOEs in large protein complexes using asymmetric deuteration: HIV‐1 gp120 in complex with a CCR5 peptide. (23rd October 2016) - Srivastava, Gautam; Moseri, Adi; Kessler, Naama; Akabayov, Sabine R.; Arshava, Boris; Naider, Fred; Anglister, Jacob
Abstract : Weak protein–protein and protein–ligand interactions play important roles in biological recognition. In many cases, simplification of structural studies of large protein complexes is achieved by investigation of the interaction between the protein and a weakly binding segment of its protein ligand. Detection of pairwise interactions in such complexes is a major challenge for both X‐ray crystallography and nuclear magnetic resonance. We demonstrate that transferred nuclear Overhauser effect (TRNOE), in combination with asymmetric deuteration of a protein and a peptide ligand can be used to detect intermolecular interactions in large protein complexes with molecular weights up to ~ 100 kDa. Using this approach, we revealed interactions between tyrosine residues of a 27‐residue peptide (deuterated at Ile and Val residues) corresponding to the N‐terminal segment of the human C‐C chemokine receptor 5 (CCR5) chemokine receptor, and a 43 kDa construct of gp120 envelope protein of human immunodeficiency virus type 1 (deuterated on all aromatics) complexed with a cluster of differentiation 4‐mimic miniprotein. The complex was present mostly as a dimer as determined by T2 relaxation measurements. The TRNOE crosspeaks in the ternary complex were assigned to the specific Tyr protons in the CCR5 peptide and to methyl protons, predominantly of isoleucine residues, and also of leucine and/or valine residues of gp120. The TRNOE/asymmetric deuteration method benefits from the sensitivity of the homonuclear NOESY experiment and does not suffer the sensitivity losses associated with isotope‐edited/isotope‐filtered approaches that rely on magnetization transfer between protons and heteronuclei that are bonded to them. The technique can be widely applied for studying large protein complexes that exhibit fast off‐rates. Abstract : Transferred NOE and asymmetric deuteration were used to determine intermolecular NOEs between aliphatic residues of gp120 and aromatic residues in the N terminus of CCR5 (Nt‐CCR5). Different deuteration combinations validated the results. The methyl groups of Ile, Leu, and/or Val of gp120 were found to interact with tyrosines and tyrosine sulfates of Nt‐CCR5(1‐27) in a weak complex with gp120 and CD4.